2011
DOI: 10.1021/ja2020185
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Gap-Mode Raman Spectroscopy on Single-Crystal Au(100) Electrodes: Tuning the Torsion Angle of 4,4′-Biphenyldithiols by an Electrochemical Gate Field

Abstract: In situ gap-mode Raman spectra were acquired in an electrochemical environment on a single-crystal gold electrode employing a Au(100)|4,4'-biphenyldithiol (BPDT)|Au-NP(55 nm) sandwich assembly. This geometry enabled an investigation of the influence of an applied electrochemical gate field on the conformational changes in nanojunctions, such as the torsion angle (φ) of molecules. A linear correlation between the intensity ratio I(C═C)/I(C(ring)-S) and cos(2) φ in 4,4'-BPDT-type molecular junctions was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
93
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 38 publications
2
93
2
Order By: Relevance
“…The size of the SERS enhancement strongly depends on the strength of the applied potential and varies for different particles, with a maximum 400% enhancement measured at the most negative potentials. This enhancement cannot be explained by the torsion of BPT molecules previously proposed 9 , since the intensity of the Raman line at 1570 cm -1 (tangential C=C stretch in the two phenyl rings) should be more affected by torsion compared to the line at 1061cm -1 (Cring-S stretching) while instead we find the same enhancements for different Raman peaks (Figure 3b). Interestingly, the applied potential has no effect on the SERS signals when insulating self-assembled molecular monolayers such as BMMBP are used as spacers (Figure 3c).…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…The size of the SERS enhancement strongly depends on the strength of the applied potential and varies for different particles, with a maximum 400% enhancement measured at the most negative potentials. This enhancement cannot be explained by the torsion of BPT molecules previously proposed 9 , since the intensity of the Raman line at 1570 cm -1 (tangential C=C stretch in the two phenyl rings) should be more affected by torsion compared to the line at 1061cm -1 (Cring-S stretching) while instead we find the same enhancements for different Raman peaks (Figure 3b). Interestingly, the applied potential has no effect on the SERS signals when insulating self-assembled molecular monolayers such as BMMBP are used as spacers (Figure 3c).…”
contrasting
confidence: 53%
“…While such chemical transformations indeed modify the plasmons, few studies examine field-induced physical changes in the surface structural and electronic configurations. Electrochemical studies tracking Raman spectroscopy within gold gaps that sandwich a single molecular layer have proposed that the potential-dependent Raman emission depends on molecular torsion angles 9 . Shifts in the scattering resonance of single Au nanoparticles following application of a negative bias have been attributed to an increase in the NP electron concentration ( ) via electron transfer from the ITO substrate 11,12 .…”
mentioning
confidence: 99%
“…In the latter case, the authors concluded that 4-chlorophenyl isocyanide adsorbs preferentially at hollow sites on Pt(111) and in the atop position on Pt(110), whilst it co-exists in both configurations at Pt(100) and Pt(211) (Figure 4(b)). Wandlowski and co-workers also used gap-mode EC-SERS to measure the influence of an applied electrochemical gate field on the molecular conformation of adsorbed dithiol molecules sandwiched in the nanogap between Au nanoparticles and Au(100) single crystal electrodes [81].…”
Section: Borrowed Ec-sersmentioning
confidence: 99%
“…A recent investigation even showed that the torsion angle thus the degree of the π-π coupling between the two phenyl rings of biphenyldithiol sandwiched between the Au nanoparticles and the single crystal gold (100) surface could be controlled by applying electrochemical gate field. 19 Nonetheless, detailed studies on the structural characteristics of biphenyldithiol on gold as well as on silver have not been reported yet to our knowledge.…”
mentioning
confidence: 99%